2014
DOI: 10.1177/0272431614556348
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Motivational Engagement at School Transition

Abstract: Adolescents typically like school less after making age-graded school transitions. Stage-environment fit theory (Eccles & Midgley, 1989) attributes this to a mismatch between developmental needs and new school environments. Our in vivo study provides a basis for future quantitative designs by uncovering the most prevalent stage-environment interactions in adolescents’ descriptions about school. Across one school year, adolescents discussed their emotional and motivational engagement. Emotional engagement (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 42 publications
(46 reference statements)
1
75
0
1
Order By: Relevance
“… More friends (Vaz, Falkmer, Parsons, et al , ; Symonds & Hargreaves, ; Neal & Frederickson, ) Positive friendships (Ashton, ) ‘Fresh start’ for sense of identity (Farmer et al , ; Davis et al , ) Friendships with older peers enhanced esteem (Symonds & Hargreaves, ) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… More friends (Vaz, Falkmer, Parsons, et al , ; Symonds & Hargreaves, ; Neal & Frederickson, ) Positive friendships (Ashton, ) ‘Fresh start’ for sense of identity (Farmer et al , ; Davis et al , ) Friendships with older peers enhanced esteem (Symonds & Hargreaves, ) …”
Section: Resultsmentioning
confidence: 99%
“… Being able to move between classes (Booth & Gerard, ; Symonds & Hargreaves, ) Increased school population (Cueto et al , ; Neal & Frederickson, ) Better and more resources (Cueto et al , Symonds & Hargreaves, ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, middle level mathematics students who perceived teacher support during the transition to the middle grades (Midgley, Feldlaufer, & Eccles, 1989) and who benefited from autonomy-supportive curriculum (Middleton et al, 2013) demonstrated higher levels of belief in the utility of mathematics. More recently, Symonds and Hargreaves (2016) investigated the complexities of academic engagement for middle level students at this transitional time, indicating how students could be both engaged and disengaged simultaneously, based on ongoing environmental and emotional factors, often relating to feelings of self-concept. Schlechty's (2011) construct of engagement, including ritual and strategic compliance, is particularly relevant for this age group, which may respond to often contradictory motivational impulses.…”
Section: Theoretical Frameworkmentioning
confidence: 99%